PERILAKU KEUANGAN CASHLESS SOCIETY PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Rahmah, Feny; Warneri, Warneri; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
A cashless society is emerging as a result of technological advancements, posing problems like consumptive behavior and financial management issues. This study aims to examine how economic education students of FKIP UNTAN manage money in a cashless society. This study employs descriptive quantitative approach. The population is divided into three groups: groups 2020, 2021, and 2022 for the 2023"“2024 semester period, which are active students registered in the Economic Education Study Program of FKIP UNTAN. The sample employed in this investigation consists of 112 respondents. Information was retrieved from observations and questionnaires distributed. Techniques for analyzing data that make use of descriptive analysis. Based on the findings, students enrolled in economic education showed a high level of financial behavior, with a rate of 71.20% in a cashless society. This was determined by calculating a number of indicators, including: (1) The consumption indicator obtained a value of 59.11% such that it falls under the category of moderate; (2) the personal financial management indicator obtained a value of 71.70% such that it falls under the category of high; (3) the pocket money allocation indicator obtained a value of 66.88% such that it falls under the category of high; and (4) the credit management indicator obtained a value of 84.35% such that it falls under the category of very high. The implication is that, in an era of a cashless society, students in economics education programs manage their money wisely and responsibly